Comprehensive Stability‑Indicating RP‑HPLC Assay of Candesartan: Method Development, Validation and Degradation Kinetics - Muskan Khanum; Priyanka. K; G. Bhavani; M. Bhaskar; K. Srivani; N. Sandhya Rani (International Journal of Pharmacy and Analytical Research, 2026)
A simple isocratic reverse‑phase HPLC (RP‑HPLC) method was developed and validated for quantitative estimation of candesartan with demonstrated stability‑indicating capability under forced degradation. Chromatographic separation was achieved on a C18 column (250 × 4.6 mm, 5 µm) using acetonitrile:0.02 M KH₂PO₄ buffer (70:30, v/v; pH 3.5 ± 0.1) at 1.0 mL/min with UV detection at 254 nm. Candesartan eluted at approximately 4.2 min with good peak symmetry. The method was linear over 2–40 µg/mL (r² = 0.9994), accurate (mean recovery 99.10–100.33%) and precise (intra‑/inter‑day % RSD ≤ 0.85%). Limits of detection and quantitation were approximately 0.2 and 0.6 µg/mL, respectively. Robustness testing showed no significant impact on assay or system suitability upon small deliberate changes in flow rate, organic composition and wavelength. Forced degradation under acidic, alkaline and oxidative conditions produced appreciable degradation, while neutral hydrolysis, thermal and photolytic stress resulted in comparatively minor changes. Kinetic evaluation suggested apparent first‑order behaviour under selected acidic and oxidative stress with estimated rate constants of 2.32 × 10⁻³ min⁻¹ (acid, 60 °C) and 2.98 × 10⁻³ min⁻¹ (oxidation, RT).